CHEMICAL COMPOSITION AND PROPHYLACTIC EFFECTS OF SATURJA KHUZESTANICA ESSENTIAL OIL ON ACUTE TOXOPLASMOSIS IN MICE - Mahmoudvand, Hossein; Beyranvand, Maryam; Nayebzadeh, Hassan; Fallahi, Shirzad; Mirbadie, Seyyed Reza; Kheirandish, Farnaz; Kayedi, Mohammad Hassan (African Journal of Traditional, Complementary and Alternative Medicines, 2017)
Background: Toxoplasma gondii is a widespread zoonotic protozoan that infects approximately one third of the global human population and all other warm-blooded animals. The present study aims to evaluate the prophylactic effects of Satureja khuzestanica essential oil (SKEO) on infected mice with acute toxoplasmosis. Materials and Methods: The components of the SKEO were identified by gas chromatography/mass spectroscopy (GC/MS). To evaluate the prophylactic effects of SKEO, mice were divided into four groups. (i) non-treated group, (ii) mice treated with olive oil once a day for two weeks, (iii) mice treated with SKEO at the dose of 0.2ml/kg once a day for two weeks, (iv) and mice orally treated with SKEO at the dose of 0.3 ml/kg once a day for two weeks. After 24 h (fifteenth day) mice in the groups of two-four were infected intraperitonealy with 10-4 tachyzoite of T. gondii, RH strain. The mortality rate in all infected mice and the number of tachyzoites from infected mice were recorded. Results: The main components of SKEO were carvacrol (78.8%), thymol (7.5%), and beta-Bisabolene (1.2%). Findings of prophylactic effects revealed that mortality rate of infected mice was 8 days after oral administration of SKEO at the concentration of 0.2 and 0.3ml/kg (P<0.05). In contrast, this value for control group was 5 days. In addition, SKEO significantly reduced the mean number of tachyzoites compared with control group (P<0.05). No significant difference (P>0.05) was observed in the clinical chemistry and hematological parameters following oral administrations of SKEO at the doses of 0.2 and 0.3 ml/kg for 14 days. Conclusion: The results showed the potential of SKEO as a natural source for the production of new prophylactic agent for use in toxoplasmosis.